Rectal Foreign Bodies: Sexual Gratification Turned Misery - Ng, Chiak Yot; Firdaus Hayati; Aishath Azna Ali; Mohd Firdaus Che Ani; Andee Dzulkarnaen Zakaria (OFFICIAL PUBLICATION OF THE MINISTRY OF HEALTH, BRUNEI DARUSSALAM, 2020)
Receiving referrals for a retained foreign body in the lower gastrointestinal tract is not something rare these days. Foreign body insertion can be classified as voluntary or involuntary which might present to the emergency department for assistance with removal. We describe a 25-year-old lady with abdominal pain and per-rectal bleeding after a retained foreign body in the rectum. She denied any peculiar activities but confessed after pelvic radiograph suggested a foreign body likely represents a self-inserted material in the rectum. Patients may present with a wide variety of symptoms but typically the history will be misleading fearing of prejudice and discrimination from the mainstream treatment. We highlight our surgical intervention and its literature review.